Social justice, epidemiology and health inequalities - Marmot, Michael (Eur J Epidemiol, 2017)
A lifetime spent studying how social determinants of health lead to health inequalities has clarified many issues. First is that social stratification is an appropriate topic of study for epidemiologists. To ignore it would be to ignore a major source of variation in health in society. Not only is the social gradient in health appropriate to study but we have made progress both in understanding its causes and what can be done to address them. Post-modern ‘critical theory’ raises questions about the social construction of science. Given the attack on science by politicians of bad faith, it is important to recognise that epidemiology and public health have a crucial role to play in providing evidence to improve health of society and reduce inequalities. Evidence gives grounds for optimism that progress can be made both in improving the health of the worst-off in society and narrowing health inequalities. Theoretical debates about ‘inequality of what’ have been helpful in clarifying theories that drive further gathering of evidence. While it is important to consider alternative explanations of the social gradient in health—principal among them reverse causation—evidence strongly supports social causation. Social action is by its nature political. It is, though, a vital function to provide the evidence that underpins action.